Облікова політика: основні аспекти - Букало, Надія Артемівна; Bukalo, Nadiia A. (Східноєвропейський національний університет імені Лесі Українки, 2016)
Статтю присвячено теоретичному обґрунтуванню та висвітленню окремих важливих елементів облікової політики. Досліджено нормативно-правове забезпечення різних аспектів облікової політики. Наведена характеристика основних нормативно-правових актів, що регламентують облікову політику в Україні. Проведено літературний пошук визначення змісту категорії «облікова політика». Розглянуто етапи формування облікової політики та основні чинників на її вплив. Досліджено теоретичні аспекти окремих важливих елементів облікової політики.The analysis of normatively – legal acts of adjusting of registration politics of enterprise is conducted in the article. The article is devoted to theoretical substantiation of certain critical accounting policies, investigated the nature and purpose of accounting policies. It is proved that the accounting policy is developed individually by each enterprise and is designed to ensure the reliability and accuracy of their financial information system. The row of factors of influence is certain on a choice and ground of registration politics. The stages of construction of registration politics are worked out. It is educed that in labours of home and foreign scientists large attention is spared to the aspects of registration politics: methodical, technical and organizational. Development and claim of registration politics are the important stage during creation of any enterprise, on the skillfully formed registration politics efficiency of management of enterprise economic activity and strategy of his development depend on the protracted prospect.
Registration politics: basic aspects
Keywords: облікова політика; облікова політика, елементи облікової політики; бухгалтерський облік; принципи; положення (стандарти) бухгалтерського обліку; registration politics; elements of registration politics; record-keeping; principles